Stat3-positive tumor cells contribute to vessels neoformation in primary central nervous system lymphoma - Ruggieri, Simona (Oncotarget, 2017)
With the aim of elucidating the relationship between Stat3 expression and tumor vessels abnormalities in the PCNLs, in this study we evaluated Stat3 and pStat3 expression by Real-time PCR and by immunohistochemistry in biopsy sections from PCNSL patients. Correlations of the expression levels with the presence of aberrant vessels were analyzed by confocal laser microscopy analysis, using FVIII as endothelial cell marker, CD133 and nestin as cancer stem cell (CSC) marker, CD20 as tumor cell marker, and Stat3. In addition, we investigated Stat3 mutations in lymphoma cells to clarify the role of the constitutive expression of Stat3 and of its phosphorylated forms. Results showed that in PCNSL, putative endothelial cells lining the vessels are heterogeneous, expressing FVIII/ pStat3/CD133 (presumably originally they are vascular progenitor cells), as well as FVIII/CD20/CD133 (presumably originally they are tumor cells). Finally, we detected a fraction of the FVIII(+) endothelial cell that co-expressed Stat3 bearing a tetraploid karyotype, while no amplification signal for the Stat3 gene was detected.